PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN LKPD UNTUK MENINGKATKAN PENCAPAIAN KOMPETENSI MATEMATIKA DAN KETUNTASAN BELAJAR SISWA KELAS XII 7 P6 SMA NEGERI 8 DENPASAR - I Kadek Oka Sudariana (Widyadari, 2025)
This study is a classroom action research that aims to determine the extent to which the application of the Problem Solving Learning Model assisted by LKPD improves the achievement of mathematical competence and learning completeness of class XII 7 P6 students of SMA Negeri 8 Denpasar in the 2024/2025 academic year. To achieve this goal, the Problem Solving Learning Model assisted by LKPD was implemented for class XII7 P6 students of SMA Negeri 8 Denpasar in the 2024/2025 academic year consisting of 52 people. The object of the study is mathematical competence and student learning completeness. Data on students' mathematical learning competence were collected using learning achievement tests. Meanwhile, data on student learning completeness were obtained by comparing students' daily test scores with the KKM score (KKM score = 70). If the score obtained by the student has reached the KKM or more, then the student is declared complete, and if it has not reached the KKM, it is declared incomplete. The percentage of students who have achieved the KKM or more indicates classical completeness. Furthermore, the data collected in this study were analyzed descriptively. The results of this study indicate that after the implementation of the Problem Solving Learning Model Assisted by LKPD, there was an increase in the achievement of students' mathematical competence, namely in cycle I the average value of students' mathematical competence reached 73.17 with classical student completion of 80.56%. Furthermore, the results achieved in the implementation of cycle II were the average value of students' mathematical competence reached 76.11 with the percentage of classical student completion reaching 91.67%.